Key service delivery processes, challenges and barriers to healthcare access for managing diabetes outside target HbA1c levels in primary care settings in Qatar: a qualitative inquiry of healthcare professionals’ and service users’ perspectives - Mohamed Ahmed Syed; Abduljaleel Abdullatif Zainel; Shajitha Thekke Veettil; Muslim Abbas Syed; Ahmed Sameer Alnuaimi (BMJ Public Health)
Introduction Globally, diabetes constitutes a major proportion of non-communicable diseases. Qatar has one of the highest prevalences of diabetes worldwide and a high proportion of people visiting non-communicable disease clinics in primary care settings have diabetes. A significant percentage of people with diabetes in Qatar have glycosylated haemoglobin (HbA1c) levels outside the target range. The aim of this study is to explore the perspectives of people with diabetes, whose HbA1c is above target range, and healthcare providers (HCPs) who are directly involved in the management of care of their disease condition within primary care settings. The key objectives of the study include highlighting the key components of service delivery mechanisms and expectations of both service care providers and people living with diabetes to identify the existing gaps and generate recommendations for improving the quality of services.Methods The study design was qualitative research. A focus group discussion was conducted among HCPs (n=23) mainly comprising family medicine physicians, ophthalmologists, dieticians, nurses, health educators and pharmacists who are directly involved in supporting (caring for) people with diabetes to manage their condition and currently working in primary health centres in the state of Qatar. People with diabetes and an HbA1c greater than 7% over the previous 6 months were recruited to participate in telephone interviews by non-probability convenience sampling. The results of the study are reported in accordance with the Consolidated Criteria for Reporting Qualitative Research and the Standards for Reporting Qualitative Research guidelines.Results The main themes that emerged from the interviews with people with diabetes included (1) desirable attributes of physician, (2) medication, (3) privacy and confidentiality, (4) exclusive services and (5) recommendations to improve the services. Among the key recommendations to improve the existing services, the HCPs emphasised the need to introduce an integrated model of care composed of a multidisciplinary team of HCPs mainly prioritising and targeting high-risk patients. The integration of medical and social models of care as well as innovative interventions such as introducing social support groups, peer support, strengthening health literacy channels, artificial intelligence-powered applications and life coaches to support people with diabetes and elevated HbA1c to improve self-management were also suggested by HCPs.Discussion Strengthening health literacy and communication channels, implementing an integrated model of care, and testing innovative interventions (such as social support groups, artificial intelligence-powered applications and life coaches) by conducting high-quality research can improve the existing healthcare services for management of diabetes. These proposed strategies can improve self-care and timely administration of medication, help achieve desired health outcomes, reduce the burden of disease and associated costs to the healthcare system and further substantiate evidence-based patient-centred care.